Idioms Relating To Colors In The Use Of Artistic Imagery In Linguistic Personality (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article presents the tools of artistic representation in today's linguistics the essence of the concept and the translation of idioms related to colours into English. Image in Uzbek and world linguistics the evaluation of tools and idioms and different approaches to this phenomenon and the done scientific things will be analysed.